The quest for sustainable polyesters - insights into the future - Vilela, Carla
Polyesters from renewable resources are an expanding area with a burgeoning scientific activity, nevertheless little has been reviewed about this particular class of polymers. The present appraisal intends to contribute to fill this literature gap by reviewing recent aspects related to the most promising renewable-based polyesters. Emphasis will be placed on bio-based polyesters that, given their comparable properties, may replace polymers derived from fossil fuel feedstock, and on bio-based polyesters with completely innovative properties for novel applications. Furthermore, the sources of renewable monomers will also be reviewed, together with the most relevant eco-friendly synthetic approaches used in polycondensation reactions leading to polyesters.